2004
DOI: 10.1007/s00467-004-1421-4
|View full text |Cite
|
Sign up to set email alerts
|

Intravenous iron therapy in pediatric hemodialysis patients: a meta-analysis

Abstract: Dialysis guidelines recommend aggressive management of anemia, including the use of intravenous iron (i.v.Fe) when indicated. However, few published data are available to guide the use of i.v.Fe in children, and studies are difficult to compare. In this meta-analysis we sought to combine evidence by pooling clinical trial data to determine if i.v.Fe therapy helped increase hematocrit, serum levels of hemoglobin, ferritin, and transferrin saturation (TSAT), and reduce erythropoietin use. We searched MEDLINE and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
17
0
2

Year Published

2007
2007
2022
2022

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 39 publications
(19 citation statements)
references
References 12 publications
0
17
0
2
Order By: Relevance
“…More rapid bolus doses of IV iron are tolerated [7] and would reduce unnecessary clinic duration. The optimum dosing regimen of IV iron has not been established for any paediatric CKD patients [1,4]. There were insufficient patients to confidently examine this issue in this series.…”
Section: Discussionmentioning
confidence: 98%
See 1 more Smart Citation
“…More rapid bolus doses of IV iron are tolerated [7] and would reduce unnecessary clinic duration. The optimum dosing regimen of IV iron has not been established for any paediatric CKD patients [1,4]. There were insufficient patients to confidently examine this issue in this series.…”
Section: Discussionmentioning
confidence: 98%
“…Intravenous (IV) iron treatment increases haemoglobin (Hb) concentration and ferritin levels and reduces erythropoietin (EPO) dose in paediatric patients on haemodialysis (HD) [1]. This effect has been reported in adult patients on peritoneal dialysis (PD) [2] and in predialysis patients [3].…”
Section: Introductionmentioning
confidence: 98%
“…Prior meta-analyses have demonstrated a clear effect of intravenous iron therapy in raising the hemoglobin level and lowering the dose of ESA in hemodialysis patients with absolute iron deficiency anemia [4,5,6]. In recent years, however, clinical trials have demonstrated a short-term benefit of intravenous iron in raising hemoglobin and lowering ESA requirement in hemodialysis patients with functional iron deficiency anemia [7,8].…”
Section: Discussionmentioning
confidence: 99%
“…Iron therapy in hemodialysis patients has traditionally been targeted to maintain the transferrin saturation (TSAT) rate >20% [1,3] and serum ferritin at 200-500 ng/ml [1,3]. Several meta-analyses have demonstrated a superior benefit of intravenous over oral iron therapy in raising the hemoglobin level and decreasing the requirement for erythropoiesis-stimulating agents (ESA) in dialysis patients with absolute iron deficiency anemia as defined by a TSAT rate <20% and serum ferritin <200 ng/ml [4,5,6]. However, in recent years, there has been a trend to administer intravenous iron to hemodialysis patients with less clear indications, i.e.…”
Section: Introductionmentioning
confidence: 99%
“…No existe actualmente un consenso respecto a la dosis y frecuencia de administración de hierro intravenoso en población pediátrica 3,62 . La dosificación apropiada es un tema complejo de establecer, principalmente porque existen escasos estudios realizados en población pediá-trica, la mayoría de los cuales incorporan un número pequeño de pacientes y fueron realizados en pacientes en hemodiálisis.…”
Section: Dosificaciónunclassified